Analisis Semiotika Roland Barthes Pesan Dakwah dalam Film Pengabdi Setan Seri Kedua Karya Joko Anwar - Faizurahman; Rodliyah Khuza’i; Hendi Suhendi (Bandung Conference Series: Islamic Broadcast Communication, 2024)
Abstract. The film "Servant Satan Series Second" directed by Joko Anwar is an important visual work that depicts events about the mystery in the complex, which shows a life full of strange events. This research aims to analyze the representation of conflict in the film "Servant of Satan Second Series" from a da'wah perspective. This research uses Roland Barthes' semiotic theory, focusing on denotation, connotation and myth in films to reveal explicit and implicit meanings. Qualitative research methods are used to examine the symbolism and representation of reality shown in films. Research findings highlight denotative meaning, such as storyline, visuals, and dialogue; connotative meaning explains subjective interpretations and cultural associations; and myth. Analysis shows that there is a main conflict represented in the film "Servant of Satan, Second Series", namely religious conflict. This research concludes that the film "Servant Satan Second Series" from a da'wah perspective acts as a medium for conveying information, ideas and da'wah messages packaged through films. And from a da'wah perspective it can raise religious awareness of the equality of mankind. Abstrak. Film "Pengabdi Setan Seri Kedua" yang disutradarai oleh Joko Anwar adalah sebuah karya visual yang penting yang menggambarkan peristiwa tentang misteri yang berada dirusun, yang memperlihatkan kehidupan yang penuh peristiwa aneh. Penelitian ini bertujuan untuk menganalisis representasi konflik dalam film "Pengabdi Setan Seri Kedua" dari perspektif dakwah. Penelitian ini menggunakan teori semiotika Roland Barthes, dengan fokus pada denotasi, konotasi, dan mitos dalam film untuk mengungkap makna yang eksplisit dan implisitnya. Metode penelitian kualitatif digunakan untuk mengkaji simbolisme dan representasi realitas yang ditampilkan dalam film. Temuan penelitian menyoroti makna denotatif, seperti alur cerita, visual, dan dialog; makna konotatif menjelaskan interpretasi subjektif dan asosiasi budaya; dan mitos. Analisis menunjukkan adanya konflik utama yang direpresentasikan dalam film "Pengabdi Setan Seri Kedua" yaitu konflik agama. Penelitian ini menyimpulkan bahwa film "Pengabdi Setan Seri Kedua" dalam perspektif dakwah berperan sebagai medium untuk menyampaikan informasi, ide, dan pesan dakwah yang dikemas melalui film. Dan dalam perspektif dakwah ia dapat mengggugah kesadaran keagamaan akan persamaan umat manusia.